Kandungan Metabolit pada Planlet Tebu (Saccharum officinarum L.) pada Perbedaan Media dan Frekuensi Subkultur - Marhamah, Yualinda Durotul; Kusdianti, Kusdianti; Surakusumah, Wahyu (Universitas Medan Area, 2025)
Sugarcane has been widely used to treat various diseases due to its metabolite content. Tissue culture is one method that can be used to produce metabolites and is an alternative biotechnology as a conservation strategy. This study aims to analyze the differences in metabolite content in sugarcane plantlets cultured with different media and subculture frequencies. Plantlets were extracted using the maceration method with 70% p.a. ethanol solvent. Metabolite analysis was carried out using a Gas Chromatography-Mass Spectrometry (GC-MS) instrument. Metabolite identification was carried out based on the NIST library. The results showed that the 10th subculture of sugarcane plantlets cultured on MS+Kinetin+Coconut Water media contained 5 metabolites, while the 11th subculture of plantlets cultured on MS+Kinetin+Tidiazuron media contained 7 metabolites. Differences in the type and number of metabolites indicate the influence of culture conditions on the metabolite profile of the plantlets. This study provides an initial overview of the potential of sugarcane tissue culture in the production of secondary metabolites.